1999
DOI: 10.1161/01.atv.19.7.1623
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin Induces Inflammatory Activation of Human Vascular Smooth Muscle Cells

Abstract: Multiple data suggest that the renin-angiotensin system contributes to the pathogenesis of atherosclerosis. The atherogenic effect of the renin-angiotensin system can only in part be explained by the influence of its effector angiotensin II on blood pressure, smooth muscle cell (SMC) growth, or antifibrinolytic activity. Because chronic inflammation of the vessel wall is a hallmark of atherosclerosis, we hypothesized that angiotensin II may elicit inflammatory signals in vascular SMCs. Human vascular SMCs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
258
2
14

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(284 citation statements)
references
References 56 publications
4
258
2
14
Order By: Relevance
“…Dechend et al reported that AT 1 -AAs induced signaling in vascular cells including AP-1 and NF-κB activation (10,11). Both of these nuclear factors participate in inflammation (23,24). Wallukat et al found monocytes, which were pivotal to vascular wall inflammatory processes, could be stimulated by AT 1 -AAs to adhere, produce tissue factor, and probably reactive oxygen species (25).…”
Section: Discussionmentioning
confidence: 99%
“…Dechend et al reported that AT 1 -AAs induced signaling in vascular cells including AP-1 and NF-κB activation (10,11). Both of these nuclear factors participate in inflammation (23,24). Wallukat et al found monocytes, which were pivotal to vascular wall inflammatory processes, could be stimulated by AT 1 -AAs to adhere, produce tissue factor, and probably reactive oxygen species (25).…”
Section: Discussionmentioning
confidence: 99%
“…16 Third, up to 30% of circulating IL-6 is produced by the adipose tissue 17,18 and the relationship between obesity and hypertension is well known. Finally, IL-6 increases collagen synthesis in the vessel wall 19 and reduces its degradation.…”
Section: Introductionmentioning
confidence: 99%
“…74,78 Angiotensin-II is known to increase VCAM-1 expression and the production of inflammatory cytokines that promote atherogenesis 79,80 (Fig. 1).…”
Section: Antihypertensive Medicationsmentioning
confidence: 99%